2020
DOI: 10.1111/1556-4029.14461
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Differentially Spliced Genes as Markers of Sex for Forensic Entomology,,

Abstract: Blow flies (Calliphoridae) are important medically and economically and are commonly used in forensics as temporal markers in death investigations. While phenotypic traits in adult flies can be sexually dimorphic, sex identification in immatures is difficult. Consequently, little is known about how sex may result in developmental disparities among sexes even though there are indications that they may be important in some instances. Since genetic mechanisms for sex are well studied in model flies and species of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 64 publications
3
25
1
Order By: Relevance
“…The transcriptome was assembled with a program designed to preserve splicing information (Sze et al, 2017), as differential splicing of key sex-determination genes is responsible for many aspects of downstream sexual dimorphism. The error structure of sequences associated with this method have already been investigated, and this algorithm has been shown to be conservative and reliable (Sze et al, 2012(Sze et al, , 2017Pimsler et al, 2019); identifying dsx in C. rufifacies, which was confirmed by Sanger sequencing (Jonika et al, 2020), and recovering known sequences in several other model and nonmodel organisms. The assembly is fragmented, which may affect its usefulness for some purposes, but for the purpose of this project it was clearly sufficient for our needs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The transcriptome was assembled with a program designed to preserve splicing information (Sze et al, 2017), as differential splicing of key sex-determination genes is responsible for many aspects of downstream sexual dimorphism. The error structure of sequences associated with this method have already been investigated, and this algorithm has been shown to be conservative and reliable (Sze et al, 2012(Sze et al, , 2017Pimsler et al, 2019); identifying dsx in C. rufifacies, which was confirmed by Sanger sequencing (Jonika et al, 2020), and recovering known sequences in several other model and nonmodel organisms. The assembly is fragmented, which may affect its usefulness for some purposes, but for the purpose of this project it was clearly sufficient for our needs.…”
Section: Discussionmentioning
confidence: 97%
“…Sex identification for each sample was performed as in Jonika et al (2020). Briefly, cDNA conversion was performed on original RNA extractions, as above, for PCR amplification of the sex specific DSX gene product.…”
Section: Gene Selection and Primer Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Genes that are expressed throughout development are associated with sex determination in C. rufifacies and the expression of genes biased toward females can be found in the eggs and adults, whereas male bias existed in pupal and larval stages of this fly (Pimsler, 2015). Specific markers for sex were identified in larvae of four species of blow flies ( L. sericata , L. cuprina , C. macellaria , and C. rufifacies ) by Jonika, Hjelmen, Faris, McGuane, and Tarone (2020), which could be useful for estimations of PMI. Pimsler et al (2019) identified genes associated with intraguild predator, C. rufifacies .…”
Section: Forensic Entomological Literature In the Southwestmentioning
confidence: 99%